Спростіть вираз (m-2) (m + 3) + (m-5) (4-m) і знайдіть його значення при m = 0,13

Спростіть вираз (m-2) (m + 3) + (m-5) (4-m) і знайдіть його значення при m = 0,13

  • (M-2) (m + 3) + (m-5) (4m) = m + 3m-2m-6 + 4m-m-20 + 5m = 10m-26 = 10 * 0.13-26 = 1.3- 26 = -24.7
  • (M-2) (m + 3) + (m-5) (4-m) = m-2m + 3m-6 + 4m-m-20 + 5m = 10m-26 = 10 * 0.13-26 = 1.3-26 = -24.7

  • Понравилась статья? Поделись с друзьями:
    Добавить комментарий

    ;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!:

    + 48 = 49